Analysis of School Policy in Improving Religious Character Through Religious Activities "Confiding with Teenagers" at NU Shofiyatul Huda Middle School - Adi Rosadi; Asep Andi Rahman; Adah Aliyah; Bambang Qomaruzzaman; Qiqi Yuliati Zaqiah (al-Afkar, Journal For Islamic Studies, 2024)
This study was motivated by the low religious character of students so that in an effort to overcome this, the school issued a policy of holding weekly activities in the form of "teenage confessions". This study aims to examine the analysis of school policies in improving religious character through religious activities "teenage confession" at NU Shofiyatul Huda Junior High School. This research uses a qualitative approach with phenomonology method. Data collection techniques are interviews and documentation. The research subjects were teachers and students with the research location at SMP NU Shofiyatul Huda while the data analysis technique was triangulation. This study found that the "Youth Curhat" activity at NU Shofiyatul Huda Junior High School is part of the school policy in deepening students' understanding of religious values. Strong support from all parties and active involvement of students and teachers in this activity reflect the school's real efforts in shaping students' religious character. A thorough evaluation process also shows the positive impact of this program in broadening students' understanding and increasing their involvement in religious activities, creating positive changes in students' attitudes and actions towards religious values in daily life.